OVERCOMING ISRAF: AN EXPLORATION OF FRUGAL LIVING WITHIN THE FRAMEWORK OF HIFDZ AL-MAL - Surya Karmila Sari; Ayu Puspa Kirana; Otong Karyono (Universitas Islam Darul 'ulum Lamongan, 2025)
This research aims to identify how the concept of frugal living can address wasteful behavior and examine its relationship with the principle of hifdz al-mal. The methodology employed is a qualitative approach through Library Research. Data were comprehensively collected by examining various sources such as books, online materials, and relevant scientific articles. The findings indicate that frugal living is consistent with the principle of hifdz al-mal, as both emphasize efficient and prudent wealth management. The implementation of frugal living aids in avoiding wastefulness and ensures that wealth management aligns with Islamic teachings as outlined in the concept of hifdz al-mal. This study concludes that the application of frugal living is effective in mitigating wasteful behavior and supports the implementation of the hifdz al-mal principle in Islamic economics. Frugal living, which emphasizes efficient and planned financial management, aligns with Islamic teachings on the prudent use of wealth. By adhering to the principles of frugal living, individuals can manage consumption by considering basic needs (dharuriyat), secondary needs (hajiyat), and complementary needs (tahsiniyat), thus preventing waste and unproductive use of resources.